Blood pressure phenotypes in young patients with type 1 diabetes - Zh. D. Kobalava; Yu. V. Stavtseva; E. A. Troitskaya; A. F. Safarova; A. E. Petrosyan (Российский кардиологический журнал)
Aim. To study phenotypes of clinic and 24-hour ambulatory blood pressure (BP), to determine their associations with arterial stiffness parameters, and to assess global cardiovascular risk (CVR) in young patients with type 1 diabetes (T1D).Material and methods. The presented cross-sectional single-center study included 81 T1D patients without a history of hypertension (HTN) and other cardiovascular diseases (CVD) (men — 39%; median age — 27 years; median duration of T1D — 6 years). All participants underwent a routine clinical and laboratory testing, measurement of clinic and 24-hour ambulatory BP (BPLab Vasotens), assessment of central BP and arterial stiffness parameters using applanation tonometry technique. BP phenotypes were analyzed with diagnostic criteria for HTN by ESC/ESH 2018 guidelines. CVR was assessed using the SCORE 10-year risk calculator (ESC 2019). The differences were considered significant at p<0,05.Results. The prevalence of true HTN was 6,2%, masked HTN — 38,3%. Isolated nocturnal HTN was revealed in 30,7% of patients with clinic BP <140/90 mm Hg. The subgroup with masked HTN was dominated by patients with normal clinic BP (58,1%) and in most cases was characterized by isolated diastolic BP increase (64,5%). Masked HTN was associated with a higher carotid-femoral pulse wave velocity (PWV) (median — 7,2 versus 6,3 m/s, p=0,002). The most common profiles of nocturnal BP decrease were non-dipper (63.9%) and night-picker (16.6%). High and very high CVR was recorded in 87,7% of patients. Conclusion. Hypertension occurs in 44,5% of young patients with type 1 diabetes and is characterized by a high prevalence of masked isolated nocturnal HTN and non-dipping. Masked HTN is associated with a higher carotid-femoral PWV. High and very high 10-year CVR was recorded in 87,7% of patients.